Experiences of diagnosis, care and treatment among Aboriginal people living with hepatitis C. (29th June 2015) - Brener, Loren; Wilson, Hannah; Jackson, L. Clair; Johnson, Priscilla; Saunders, Veronica; Treloar, Carla
Abstract: Objective: Aboriginal Australians are disproportionately affected by hepatitis C (HCV). There are a range of barriers to HCV care, often beginning with poor diagnosis experiences. Little research exists on the experiences of Aboriginal Australians living with HCV. This study aimed to describe their patterns of HCV care and treatment with specific emphasis on the impact of their being informed of their diagnosis in a culturally sensitive manner. Methods: A total of 203 Aboriginal people living with HCV were recruited to complete a survey assessing experiences of HCV testing and care, HCV knowledge, lifestyle changes after diagnosis, perceived stigma and discrimination. Results: Of the sample, 58% were male and 96% identified as Aboriginal, with a mean age of 28 years. Correlation analysis revealed that satisfaction with the cultural appropriateness of the diagnosis was associated with: being offered pre‐ and post‐test counselling; satisfaction with HCV care; decreased feelings of HCV‐related stigma; lower scores on the medical mistrust scale; and greater intentions to access HCV treatment. Conclusions: These findings confirm the importance of providing a HCV diagnosis in a culturally appropriate way for Aboriginal people. Implications: Satisfaction with HCV diagnosis appears essential in establishing patterns of greater engagement with HCV care and treatment for this group.